Biochemical and Hepatoprotcetive Effects of Pure Cinnamic acid Against Cyclophosphamide in White Mice - Nibal, Kh. Mousa; Labeeb, Ah. , Al-Zuubaidi; Iman I. Qatia; Ishrak, Ab. Ahmed (Journal of Madenat Alelem University College, 2011)
The study was carried out to determine hepatotoxicity and hepatoprotcetive effects for Cinnamic acid in comparison with vitamin C against the mutagenic influence of cyclophosphamide, a chemical compound that damage hepatic cells and has mutagenic effects .The effect was studied in mammalian system invivo depended on evaluating the enzymatic activity of three hepatic enzymes: Alanine Transaminase (ALT), Aspartate Transaminase (AST), and Alkaline Phosphate (ALP). Two concentrations of pure cinnamic acid (5.6 and 2.8 mg/kg) were evaluated to choose the suitable concentration which remembered the negative control. An interaction experiments, included two types of treatments pre-cyclophosphamide and post-cyclophosphamide was carried out in order to determine the mechanisms of the pure cinnamic acid. Results showed no toxic and hepatotoxicity influence in biological system and instead it showed highly performance in preventing or reducing the hepatotoxicity of cyclophosphamide. Cinnamic acid increased the ALT, AST and ALP especially in dose 2.8 mg/kg. The positive effect was higher when pure cinnamic acid was used as post- cyclophosphamide treatments and to less extent in pre-cyclophosphamide treatments. Therefore, cinnamic acid can be considered as a cure hepatocytes from acute liver damage at first degree and responsible at the second degree as a cardiac, skeletal muscle and placental tissue protective.